HUBUNGAN POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN BATITA - Muthmainnah Muthmainnah; Meilan Meilan; Yeni Mulyani (CNJ: Caring Nursing Journal, 2020)
family is the most important part of the growth and development of toddlers. Family parenting is very influential on the character formation of toddlers. Every family usually has different parenting styles for toddlers. Parenting also affects the success of the family in transferring and instilling religious values, goodness, and norms. Parenting for toddlers is a process of interaction between parents and toddlers. The aim is to know the relationship between parenting style and toddler development. This type of research is a quantitative study with a correlational descriptive design. Correlational descriptive method, with a cross sectional approach. The population in this study were all parents who had toddlers aged 1-3 years as many as 177 respondents, while the sample in this study were 123 respondents who had toddlers aged 1-3 years. By using purposive sampling technique. The results showed that the majority of parenting styles were in good category as many as 74 people (60.2%), the majority of children development was normal category as many as 101 children (82.1%), there was a relationship between parenting styles and the development of toddlers p = 0.000 with a value α = 0.05, then p <α, with the Coofficien Correlation value = 0.361 or having a weak relationship and positive direction of the relationship. Parenting style is very important in the growth and development of toddlers. The intensity of the closeness of parents in communication and others also needs to be considered